PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA KARYAWAN PUSAT STUDI JEPANG STEAK KILOAN - Mardhatillah, Fitri Marshanda (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
Basically, rewards and punishments are both needed to improve employee work results, including motivating employees to achieve agency goals. Both are reactions from a leader to the performance and productivity shown by his subordinates, punishment for bad deeds and rewards for good deeds. Looking at their functions, it seems that both are opposites, but in essence they both aim to make someone better, including motivating employees to work. Rewards have a significant effect on employee work motivation at the Steak Kiloan Japanese Study Center, meaning that the provision of rewards in the company is appropriate and considered sufficient so that it can improve the welfare of its employees that with rewards it triggers employees to be enthusiastic about working or motivates employees to complete their work. In this study, the author used a survey method, namely research that collects information to represent the entire population. The results of the partial test of the positive t-count value of 4,633 and a significance value of 0.002 so that it can be concluded that the reward variable has a positive and significant effect on work motivation (Y). Significant work motivation. The partial test results of the positive tvalue of 4.633 and the significance value of 0.000 can be concluded that Punishment has a positive and significant effect on Work Motivation. Based on the simultaneous f-test table, the f-table value is 3.245, which means that Fcount> F-table where 63.219> 3.245 so it can be concluded that F-count> F-table where 63.219> 3.245. It can be concluded that simultaneously all independent variables (Reward and Punishment) have a positive and significant effect on the dependent variable (Work Motivation).